The utility of polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS) in surface and in situ studies: new data processing and presentation approach. Issue 11 (3rd May 2018) - Monyoncho, Evans A.; Zamlynny, Vlad; Woo, Tom K.; Baranova, Elena A.
Abstract : Infrared spectroscopy is a powerful non-destructive technique for the identification and quantification of organic molecules widely used in scientific studies. Abstract : Infrared spectroscopy is a powerful non-destructive technique for the identification and quantification of organic molecules widely used in scientific studies. For many years, efforts have been made to adopt this technique for the in situ monitoring of reactions. From these efforts, polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS) was developed three decades ago. Unfortunately, because of the complexity of data processing and interpretation, PM-IRRAS had been avoided in lieu of the single potential alteration infrared spectroscopy (SPAIRS) and subtractively normalized interfacial Fourier transform infrared (SNIFTIR). In this work, we present a new approach for PM-IRRAS data processing and presentation, which provides more insight into in situ and surface studies besides dramatically improving the S/N. In this new approach, we recommend three complementary methods of data treatment (eqn (7), (9) and (10)) as the new protocols for presenting PM-IRRAS data. These equations are robust in visualising the surface processes at the solid–liquid and solid–gas interphases. Eqn (7) contrasts the surface adsorbed species with respect to the isotropic background with or without the influence of the applied potential. Eqn (9) highlights the surface potential-driven changes between the sample and the reference spectra. Eqn (10) focuses on the bulk-phase (solution/gas and surface species) potential-driven changes between the sample and the reference spectra, and hence it can be used to track the production of species, which desorb from the surface upon their formation. Examples of ethanol electro-oxidation reaction are provided as a test system for in situ studies and PVP deposited on glassy carbon for thin-film studies to illustrate the utility of the new PM-IRRAS data handling protocol, which is poised to improve the understanding of the chemistry and physics of surface processes.